Mosque architecture: present issues and future ideas (عمارة المسجد: قضايا الحاضر وأفكار المستقبل) - Al-Naim, Mashary A. (Abdullatif Al Fozan Award for Mosque Architecture and Institut Terjemahan & Buku Malaysia Berhad, 2019)
This multilayered conflict is traced from the interrelationship between mosques and their surrounding urban contexts, including their visualization and spatial distribution, especially related to daily practice (ablution rooms, shoe lockers, etc.). Therefore, these things reflect the general attitude to prayer and point to the importance of sustainability for water and energy resources. Since mosques are urban buildings of distinguished sanctity (3.6 million mosques), it is natural they are a worthy urban study topic. Therefore, this conference tackles this interdisciplinary issue with the consultation of several experts in one location.